111k views
4 votes
Hello! Need a little help on this question, thank you!

Hello! Need a little help on this question, thank you!-example-1
Hello! Need a little help on this question, thank you!-example-1
Hello! Need a little help on this question, thank you!-example-2
User Lpiepiora
by
4.9k points

1 Answer

5 votes

Solution

Given


\begin{gathered} f(x)=\log_2(x)+2 \\ \\ g(x)=\log_2(x^3)-6 \\ \\ h(x)=\log_2(x)+2+\log_2(x^3)-6=\log_2(x* x^3)-4=\log_2(x^4)-4 \\ \\ =4\log_2(x)-4=4(\log_2(x)-\log_2(2))=4(\log_2((x)/(2))) \\ \\ or\text{ }4\log_2(x)-4 \end{gathered}

User Agnessa
by
4.7k points